2007
DOI: 10.1177/019027250707000206
|View full text |Cite
|
Sign up to set email alerts
|

Identity Change in Newly Married Couples: Effects Of Positive And Negative Feedback

Abstract: Previous research has examined individuals' relative preference for consistent and enhancing feedback by examining reactions to negative and positive feedback. Recent research shows that, in general, individuals prefer feedback that is consistent with self-views, even if feedback is negative. It is unclear, however, whether negative and positive feedback equally affect actual changes in individuals' self-views. Using insights from Identity Control Theory (Burke 1991(Burke , 1996 and a sample of newly married c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
(40 reference statements)
2
12
0
Order By: Relevance
“…In the research presented here, we offer one possible way to incorporate emotions as an input, or source of information, into the IT model of the self. Consistent with previous research (Cast and Cantwell ), a discrepancy between an individual's identities and his or her spouse's views leads to change in identity. In addition, we find that positive and negative feedback equally influence identity change, further supporting self‐consistency motivations (see also Burke and Harrod ; Cast and Cantwell ) rather than self‐enhancement motives (e.g., Tesser ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the research presented here, we offer one possible way to incorporate emotions as an input, or source of information, into the IT model of the self. Consistent with previous research (Cast and Cantwell ), a discrepancy between an individual's identities and his or her spouse's views leads to change in identity. In addition, we find that positive and negative feedback equally influence identity change, further supporting self‐consistency motivations (see also Burke and Harrod ; Cast and Cantwell ) rather than self‐enhancement motives (e.g., Tesser ).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, research finds that identity standards change in response to the views of others, becoming more consistent with others' views (Cast et al. ; Cast ; Cast and Cantwell ). Thus, consistent with other research, we hypothesize that:…”
Section: Identity Changementioning
confidence: 99%
See 1 more Smart Citation
“…When behavior meanings do not match identity standard meanings, reflected appraisals (the meanings that others are attributing to the self in the situation) may either exceed or fall short of one's identity standard meanings. Research has studied whether identity change is more likely to occur when reflected appraisals meanings are higher or lower than identity standard meanings (Cast & Cantwell, 2007). They found that when the reflected appraisals do not match the identity standard, peoples' identities slowly change in the direction of the discrepant reflected appraisals, but individuals also successfully acted to change the reflected appraisals over time.…”
Section: Identity Changementioning
confidence: 99%
“…This results in positive emotions and self-perceptions and may enhance a man's commitment to the identity (Collett et al 2015). Any perceived mismatch, on the other hand, indicates self-discrepancy, generates negative emotion, and will either prompt increased efforts at involvement or lead a father to alter or abandon the identity either cognitively or behaviorally (Burke and Harrod 2005;Cast and Cantwell 2007).…”
Section: The 'Good Father'mentioning
confidence: 99%